PERAN GURU DALAM MENJAGA PENDIDIKAN NASIONAL DAN NILAI AGAMA DI ERA DIGITAL - Fathanah, Isma; Hanifa, Zahra Aulia; Al Munawar, Agil Husein; Sauri, Sofyan (Pedagogi: Jurnal Ilmiah Pendidikan, 2025)
The digital era brings great challenges to national education and religious values, where teachers play a central role as moral guides, character educators, as well as innovators in the learning process. This study aims to examine the role of teachers in maintaining the relevance of religious education and national values amid rapid technological development. Using a qualitative approach through the literature study method, this research analyzes the use of technology as a learning support tool, including digital media, technological literacy, and interaction-based learning strategies. The results show that the wise integration of technology can be an effective tool in shaping character and strengthening students' religious values, as long as it is supported by adequate digital literacy. Teachers are required to be able to direct students to utilize technology positively, understand religious teachings deeply, and apply them in everyday life. This study concludes that teachers not only act as knowledge conveyors, but also as facilitators, innovators, and moral guides who ensure that religious education remains strong, relevant, and adaptive in the digital era.